Dialogue between civil contract law and traditional African law: an essay on Nsountee in the Ngombale community of West Cameroon - (:unkn) unknown (My University, 2022)
This preliminary study on the Nsountee in the Ngombale community of West Cameroon, as an essay in the theory of literature, constitutes an unfinished project that is part of a global study of the concepts of contract and law in indigenous laws here and elsewhere. It aims to highlight the richness of the possibilities available to the law as intercultural phenomenon. By considering a natural and spontaneous law, specific to the practice of Nsountee, we try to mitigate the rigour of the rules of civil law to establishing a dialogue between various juridical discourses developing in contract law. This leads to the idea of contract as a social artefact. Therefore, the question for jurists would be to establish whether a recourse to an exotic law (oral law, indigenous law, non-civil law) can contribute to enriching our understanding of the contract in civil law. We consider here a possibility of its enrichment by indigenous law which is being rehabilitated in a postcolonial context of interculturality and normative pluralism. We rely on the fact that the invisibilization, delegitimization or illegalization of indigenous laws, for a long time decreed as not in force (non-law, anti-law, infra-law) by the dominant legal order, the positive state law inherited from colonization, is gradually giving way to a pacific coexistence. As a postcolonial or critical legal study (legal narrativism), the essay also “tries” to tell the story of a traditional African contract law and provoke reflection on the contractual dogma of modern law.
Keywords: African Research